THU0435 Treatment Persistence with Subcutaneous Biologic Therapies in Patients with Psoriatic Arthritis (PSA). (9th June 2015) - Lyu, R.; Ding, Q.; Govoni, M.; Makin, C.; Korn, J.; Fan, T.; Ogbonnaya, A.; Black, C.M.; Kachroo, S.
Abstract : Background: The treatment landscape of psoriatic arthritis has evolved in recent years, with the introduction of subcutaneous TNF-alpha blockers in the EU. These changes in the treatment landscape could affect how patients are managed with psoriatic arthritis. Objectives: The objective of this study was to describe persistence with subcutaneous biologic over 12 months for newly treated PsA patients and evaluate the impact of prior DMARD use Methods: This was a retrospective analysis using IMS Disease Analyzer-Germany, an electronic medical records database. Adult (≥18 years of age) PsA patients who initiated therapy with subcutaneous biologics between January 1, 2009 and June 30, 2012 were included in the analysis. The first subcutaneous biologic prescription date served as their index date. Continuous observation of at least 12 months pre- and post-index date was required. Patients who were prescribed any biologic during the pre-index period or diagnosed with rheumatoid arthritis, ankylosing spondylitis, Crohn's disease, or ulcerative colitis during the study period were excluded from the study population. A chi-square test was used to measure differences between patients with and without use of pre-index DMARD. A multivariate logistic regression was created to assess the impact of DMARD use on persistence, controlling for baseline characteristics Results: A total of 197 biologic-naïve PsA patients were selected. Of these, 89 were free of PsO. The mean (SD) age of the patients was 49 (11) years, with 50% being female. The majority of patients (61%) indexed on adalimumab, while the remainder indexed on etanercept (35%) and golimumab (4%). In the overall PsA population, the persistence rate with the index subcutaneous biologic was 54.3%, with similar results among those with and without DMARD uses (53% vs 56%, respectively). Multivariate analysis did not identify any significant predictors for persistence, including DMARD use (OR: 1.05; 95% CI: 0.53-2.07) and psoriasis (OR: 1.07; 95% CI: 0.56- 2.03 Conclusions: More than half of the PsA patients were persistent with the index subcutaneous biologic over a 12-month period with similar persistence rates observed among those with and without psoriasis and DMARD use Disclosure of Interest: R. Lyu Employee of: Merck, Q. Ding Employee of: Merck, M. Govoni Employee of: Merck, C. Makin: None declared, J. Korn: None declared, T. Fan Employee of: Merck, A. Ogbonnaya: None declared, C. Black Employee of: Merck, S. Kachroo Employee of: Merck